Synthesis and Characterization of Paclitaxel-Loaded Silver Nanoparticles: Evaluation of Cytotoxic Effects and Antimicrobial Activity - Tutku Tunç; Ceylan Hepokur; Afşin Kari̇per (Bioinorganic Chemistry and Applications)
Carrier system therapies based on combining cancer drugs with nanoparticles have been reported to control tumor growth and significantly reduce the side effects of cancer drugs. We thought that paclitaxel-loaded silver nanoparticles (AgNPs-PTX) were the right carrier to target cancer cells. We also carried out antimicrobial activity experiments as systems formed with nanoparticles have been shown to have antimicrobial activity. In our study, we used easy-to-synthesize and low-cost silver nanoparticles (AgNPs) with biocatalytic and photocatalytic advantages as drug carriers. We investigated the antiproliferative activities of silver nanoparticles synthesized by adding paclitaxel on MCF-7 (breast adenocarcinoma cell line), A549 (lung carcinoma cell line), C6 (brain glioma cell line) cells, and healthy WI-38 (fibroblast normal cell line) cell lines and their antimicrobial activities on 10 different microorganisms. The synthesized AgNPs and AgNPs-PTX were characterized by dynamic light scattering (DLS), scanning transmission electron microscopy, UV-visible spectroscopy, Fourier transform infrared spectroscopy, and X-ray spectroscopy. The nanoparticles were spherical in shape, with AgNPs ranging in size from 2.32 to 5.6 nm and AgNPs-PTXs from 24.36 to 58.77 nm. AgNPs demonstrated well stability of −47.3 mV, and AgNPs-PTX showed good stability of −25.4 mV. The antiproliferative effects of the synthesized nanoparticles were determined by XTT (tetrazolium dye; 2,3-bis-(2-methoxy-4-nitro-5-sulfenyl)-(2H)-tetrazolium-5-carboxanilide), and the proapoptotic effects were determined by annexin V/propidium iodide (PI) staining. The effect of AgNPs-PTX was more effective, and anticancer activity was higher than PTX in all cell lines. When selectivity indices were calculated, AgNPs-PTX was more selective in the A549 cell line (SI value 6.53 μg/mL). AgNPs-PTX was determined to increase apoptosis cells by inducing DNA fragmentation. To determine the antimicrobial activity, the MIC (minimum inhibitory concentration) test was performed using 8 different bacteria and 2 different fungi. Seven of the 10 microorganisms tested exhibited high antimicrobial activity according to the MIC ≤100 μg/mL standard, reaching MIC values below 100 μg/mL and 100 μg/mL for both AgNPs and AgNPs-PTX compared to reference sources. Compared to standard antibiotics, AgNPs-PTX was highly effective against 4 microorganisms.